Penerapan Metode Dewey Decimal Classification Pada Pembuatan Aplikasi Persewaan Pakaian Berbasis Website Pada UMKM Tyas Aulia - Tiowati, Sulis; Firdaus, Mirza Aulia; Setyawan, Henry Bambang; Budiardjo, Hardman; Arifin, Mochammmad (Universitas Multi Data Palembang, 2024)
UMKM Tyas Aulia is an UMKM engaged in clothing rental services. The problem with the current Tyas Aulia UMKM is that customers have to come and there is no grouping of clothes based on clothing categories so that searching for clothes takes a long time. Therefore, in this study, a website-based clothing rental application was made at Tyas Aulia UMKM using the Dewey Decimal Classification method as a numbering system to classify clothes based on clothing categories. Based on the results of testing with the Blackbox Testing method, it is found that all functions have run well. While the results of User Acceptance Testing obtained a percentage of 90% that this application can help the admin in managing clothes. In addition, a percentage of 94% was obtained that the application that has been built can help customers to rent clothes online.